Humanidades digitais e cultura material (escolar) - Vidal, Diana (History of Education in Latin America - HistELA, 2022)
The article addresses the relationship between digital humanities and research in the history of education, taking material culture as a problem. It is structured in three parts. Initially, I approach the recent debates around the structuring concepts of historical knowledge - space and time - considered in its material dimension. In the second section, I focus on the raw material of the historiographical operation – the sources – interrogated from its new materiality. Finally, I trace some reflections on the result of the historiographical operation – writing in the history of educstion – digital environments.